Guggulosomes: A herbal approach for enhanced topical delivery of phenylbutazone - Vivek Dave; Renu Bala Yadav; Shipra Gupta; Swapnil Sharma (SpringerOpen, 2017)
Background: Guggul, the gum resin obtained from Commiphora mukul, is one of the components of various formulations of traditional Ayurvedic medicine to treat inflammation, atherosclerosis, and weight loss. This research work describes Guggul lipid as a carrier and synergistic effect for anti-inflammatory drugs. Method: Guggulosomes prepared by trituration method was further incorporated into carbopol gel, developed for the enhanced topical drug delivery system for the phenylbutazone. This preparation was characterized by using Attenuated total reflection- Fourier transform infrared spectroscopy (ATR-FTIR), Scanning electron microscopy (SEM), Atomic force microscopy (AFM), Differential scanning calorimeter (DSC), Thermogravimetric analysis (TGA), Particle size & Zeta potential and further guggulosomes was tested for Anti-inflammatory activity and % cumulative drug release. All these study was carried out by using standard protocol. Results: The guggulosomes shows all the characteristic peaks in ATR-FTIR. The optimized formulation was spherical in shape having diameter >200 nm. The % entrapment efficiency was 77.2 ± 0.212 with good % Cumulative drug release 60.80 ± 0.707%. The anti-inflammatory activity of the optimized formulation was found satisfactory (89%). Conclusion: The guggulosomes prepared by trituration method was found to give a synergistic effect along with the phenylbutazone when incorporated into the carbopol gel. Thus, this present research shows that it can be good perspective for enhanced topical drug delivery system.